The designing of 3D-printed modular artificial reefs through design thinking framework: a case study in Koh Khai, Chumphon Province, Thailand - Torpong Limlunjakorn (Discover Sustainability, 2025)
Coral reefs degradation in Thailand demands scalable, community-accessible restoration solutions. This study addresses the limitations of conventional artificial reefs by developing 3D-printed modular artificial reefs (3DMARs) optimized for ecological performance, usability, and low-resource deployment. Formulated through the lens of design expertise and applying a design thinking framework, the research integrates qualitative content analysis, interdisciplinary collaboration, and user-centered design to establish key criteria, including modularity, flexibility, and environmental sustainability. Prototypes were co-developed with SCG Co., Ltd. Field deployment at Koh Khai, Chumphon Province, demonstrated ease of transport, manual installation, and ecological compatibility. Initial observations suggest that the system enhances coral habitat complexity while promoting local engagement. The study presents a replicable and adaptable model for decentralized reef restoration, supporting sustainable marine efforts in regions with limited technical capacity, such as Thailand and similar Southeast Asian coastal areas.
Keywords: Coral and Marine Ecosystems Studies; Microplastics and Plastic Pollution; Coastal and Marine Management